2017
DOI: 10.5539/jas.v9n12p30
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selected Plant Growth Regulators on Yield and Stem Height of Spring Wheat in Ontario

Abstract: Lodging is an important limiting factor in wheat because it affects growth, yield and grain quality. Plant growth regulators (PGRs) are often used to restrain elongation of internodes, improve lodging traits, and protect yield potentials. An experiment was set up in the greenhouse at the Ottawa Research and Development Centre (ORDC) to study the effect of the selected PGRs (Manipulator, the active ingredient of which is chlormequat; and Palisade, the active ingredient of which is trinexapac-ethyl) on yield, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 32 publications
2
26
2
Order By: Relevance
“…A chronic worldwide constraint to sustainable wheat production is lodging that often decreases photosynthetic ability and biomass production, deteriorates seed quality, and creates difficulties to harvest operations (Zhang et al,2017) Wheat and rice are highly prone to lodging during late vegetative growth and at reproductive stages ( Shah et al, 2019) exaggerating the need for additional research efforts Lodging in cereals can be defined as the permanent displacement of stems from the vertical position, which could result from either plastic failure of the stem base (stem lodging) or failure of the belowground anchorage system (Berry et al, 2004). The key reasons responsible for wheat lodging are increase in weight of mature ears due to water accumulation, occurrence of high speed winds at grain filling stage, wide use of flat planting and flood irrigation and the lack of acceptable cultivars of wheat that are lodging tolerant at higher nitrogen (N) rates etc.…”
Section: Issn: 2319-7706 Volume 10 Number 01 (2021)mentioning
confidence: 99%
See 2 more Smart Citations
“…A chronic worldwide constraint to sustainable wheat production is lodging that often decreases photosynthetic ability and biomass production, deteriorates seed quality, and creates difficulties to harvest operations (Zhang et al,2017) Wheat and rice are highly prone to lodging during late vegetative growth and at reproductive stages ( Shah et al, 2019) exaggerating the need for additional research efforts Lodging in cereals can be defined as the permanent displacement of stems from the vertical position, which could result from either plastic failure of the stem base (stem lodging) or failure of the belowground anchorage system (Berry et al, 2004). The key reasons responsible for wheat lodging are increase in weight of mature ears due to water accumulation, occurrence of high speed winds at grain filling stage, wide use of flat planting and flood irrigation and the lack of acceptable cultivars of wheat that are lodging tolerant at higher nitrogen (N) rates etc.…”
Section: Issn: 2319-7706 Volume 10 Number 01 (2021)mentioning
confidence: 99%
“…The yield potential of high yielding genotypes of wheat under irrigated and high input rates could be achieved consistently and efficiently by finding suitable solutions of lodging problem. In this context, the use of growth retardants found to be most effective for managing the problem of lodging (Zhang et al, 2017). Growth retardants are chemical substances that have the potential to alter structural or vital processes inside the plant by modifying hormone balance to increase yield, improve quality or facilitate harvesting through checking lodging especially in cereals (Zhang et al, 2017).…”
Section: Issn: 2319-7706 Volume 10 Number 01 (2021)mentioning
confidence: 99%
See 1 more Smart Citation
“…[30] argued that a significant increase in the seed yield of red fescue despite the lack of significant effects on straw length suggests that TE had an influence on the physiological processes affecting yield. A study on the application of TE on wheat showed that TE increased leaf relative chlorophyll content of the plant [31]. TE applied on creeping bentgrass increased relative water content and chlorophyll content.…”
Section: Discussionmentioning
confidence: 99%
“…A research on wheat enables a deeper understanding of the impact of PGRs on the morphological traits of plant's internodes and lodging. According to Zhang [31], the use of TE increased the stem strength (second basal internode), stem diameter, wall thickness, and also, enhanced lodging resistance at the anatomical level of the plants. Moreover, TE was extremely effective in reducing plant height.…”
Section: Discussionmentioning
confidence: 99%